High Mg/Ca Molar Ratios Promote Protodolomite Precipitation Induced by the Extreme Halophilic Bacterium Vibrio harveyi QPL2 - Han, Zuozhen; Qi, Peilin; Zhao, Yanyang; Guo, Na; Yan, Huaxiao; Tucker, Maurice E.; Li, Dan; Wang, Jiajia; Zhao, Hui (Frontiers in Microbiology, 2022)
Bacterial activities have been demonstrated as critical for protodolomite precipitation in specific aqueous conditions, whereas the relationship between the various hydrochemical factors and bacterial activity has not been fully explored. In this study, biomineralization experiments were conducted using a newly isolated extreme halophilic bacterium from salina mud, Vibrio harveyi QPL2, under various Mg/Ca molar ratios (0, 3, 6, 10, and 12) and a salinity of 200 ‰. The mineral phases, elemental composition, morphology and crystal lattice structure of the precipitates were analyzed by XRD, SEM and HRTEM, respectively. The organic weight and functional groups in the biominerals were identified by TG-DSC, FTIR, and XPS analysis. The amounts of amino acids and polysaccharides in the EPS of QPL2 cultured at various Mg/Ca molar ratios were quantified by an amino acid analyzer and high-performance liquid chromatography. The results confirm that disordered stoichiometric protodolomite was successfully precipitated through the activities of bacteria in a medium with relatively high Mg/Ca molar ratios (10 and 12) but it was not identified in cultures with lower Mg/Ca molar ratios (0, 3, and 6). That bacterial activity is critical for protodolomite formation is shown by the significant bacterial relicts identified in the precipitated spherulite crystals, including pinhole structures, a mineral coating around cells, and high organic matter content within the crystal. It was also confirmed that the high Mg/Ca molar ratio affects the composition of the organic components in the bacterial EPS, leading to the precipitation of the protodolomite. Specifically, not only the total EPS amount, but also other facilitators including the acidic amino acids (Glu and Asp) and polysaccharides in the EPS, increased significantly under the high Mg/Ca molar ratios. Combined with previous studies, the present findings suggest a clear link between high Mg/Ca molar ratios and the formation of protodolomite through halophilic bacterial activity.